Integrasi Kompetensi Auditor dan Pengendalian Internal dalam Membangun Kualitas Audit pada Perusahaan Pembiayaan - Rudi Ananda (Ebisma (Economics, Business, Management, & Accounting Journal), 2026)
Increasing risk complexity and governance demands in financing companies make audit quality a critical aspect of financial reporting credibility. Audit effectiveness is influenced not only by auditor competence but also by the quality of internal control systems that support information reliability and organizational oversight. This study examines the effect of auditor competence and internal control on audit quality and the mediating role of internal control. Data were collected through a survey of auditors and related personnel in financing companies in South Sumatra Province and analyzed using covariance-based Structural Equation Modeling with AMOS. The results show that auditor competence positively affects internal control and audit quality. Internal control also positively affects audit quality and mediates the relationship between auditor competence and audit quality. These findings confirm that audit quality is shaped by the integration of auditor competence and effective internal control